Moderators of the coach leadership and athlete motivation relationship - Lopez de Subijana, C.; Martin, L. J.; McGuire, C. S.; Coté, J. (European Journal of Sport Science, 2023)
The purpose of this study was to determine whether the relationship between coach leadership and athlete motivation was moderated by age, gender, competition level, and seasons spent with a coach. This study involved data from two previous studies that explored this relationship yet provides a novel perspective through the lens of important moderators. Three-hundred and three athletes (Mage = 17.6 years; SD = 3.20; 49.7% women and 50.3% men) responded to questionnaires pertaining to their coaches` leadership behaviours and their own sport motivation. Multiple regression analyses using moderators were conducted. Age, competition level, and seasons spent with the coach significantly moderated the relationships of interest. Coach transformational leadership predicted intrinsic and extrinsic motivation to a greater extent when athletes were younger than 20.8 and 18.2 years of age, respectively. Further, coach transactional leadership predicted intrinsic and extrinsic motivation to a greater extent when athletes had trained for more than two seasons with their coach. Results emphasize the need to consider athlete characteristics from both research and practitioner perspectives. Herein, we advocate for increased awareness amongst key sport stakeholders on the influence that a coach can have on younger athletes` motivation and the importance of developing coach-athlete relationships over time.